The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/rhc3.12263
|View full text |Cite
|
Sign up to set email alerts
|

What drives feelings of responsibility for disaster preparedness? A case of power failures in Finland and New Zealand

Abstract: The division of responsibilities for disaster preparedness between individuals and society is rapidly evolving: national‐level preparedness has made way for networked disaster risk governance, and citizens are also expected to play their part. Preparedness is shaped by various individual and socioeconomic factors, including previous disaster experience and perceptions of risk. However, little is known about whom citizens perceive to be responsible for preparedness. This study examines the factors associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 68 publications
1
0
0
Order By: Relevance
“…A question that often arises is who is responsible to take preparedness actions. People who do not experience disasters often tend to believe that (regional) authorities and civil protection are responsible to ensure that communities are resilient to earthquakes (Nikkanen et al, 2023). This is supported by our findings that people indicated that the risk map is especially useful for emergency services/authorities and not for themselves.…”
Section: Insights For Information Campaignssupporting
confidence: 74%
See 1 more Smart Citation
“…A question that often arises is who is responsible to take preparedness actions. People who do not experience disasters often tend to believe that (regional) authorities and civil protection are responsible to ensure that communities are resilient to earthquakes (Nikkanen et al, 2023). This is supported by our findings that people indicated that the risk map is especially useful for emergency services/authorities and not for themselves.…”
Section: Insights For Information Campaignssupporting
confidence: 74%
“…Further, the lowest label of the legend should not be "no risk" but rather "very low risk". Communicating that zero risk is impossible does not diminish the trust in risk management agencies, so there is no need to fear losing people's confidence in the information provided (Nakayachi, 1998).…”
Section: Insights For Information Campaignsmentioning
confidence: 99%
“…Indeed, research into preparedness has documented that preparedness tends to increase after communities are affected by disaster (Kapucu, 2008). This is also what Nikkanen et al (2023) find in their contribution to this issue. The authors investigated what drives the feeling of responsibility for disaster preparedness between individuals and society in a large‐scale survey.…”
supporting
confidence: 83%
“…Integrating wider public participation could diversify perspectives and challenge the consensus, as well as contribute to the goal of whole-of-society vision of comprehensive security. In addition, strengthening the role of citizens could also boost their perception of responsibility regarding preparedness, and thus contribute to household preparedness [38].…”
Section: Discussionmentioning
confidence: 99%